A partnership to assess clinical nurse leadership skills. Issue 4 (April 2018) - Logrippo, Maria; Kelly, Sarah; Sardinas, Nicole; Naft, Molly
Abstract : Read about this quality improvement project that was developed to establish appropriate leadership training and education, and advance nursing research, at a large academic medical center.